Interdisciplinary Unsettlings of Place and Space Conversations, Investigations and Research - Pinto, Sarah; Hannigan, Shelley; Walker-Gibbs, Bernadette; Charlton, Emma.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
This book brings together researchers from different fields, traditions and perspectives to examine the ways in which place and space might (be) unsettle(d). Researchers from across the humanities and social sciences have been drawn to the study of place and space since the 1970s, and the term 'unsettled' has been an occasional but recurring presence in this body of scholarship. Though it has been used to invoke a range of meanings, from the dangerous to the liberating, the term itself has rarely been at the centre of sustained examination. This collection highlights the idea of the unsettled in the scholarly investigation of place and space. The respective chapters offer a dialogue between a diverse and eclectic group of researchers, crossing significant disciplinary and interdisciplinary boundaries in the process. The purpose of the collection is to juxtapose a range of different approaches to, and perspectives on, the unsettling of place andspace. In doing so, Interdisciplinary Unsettlings of Place and Space makes an important contribution and offers new insights into how scholarship and research into different fields and practices may help us re-envision place and space.
Interdisciplinary Unsettlings of Place and Space: An Introduction to the Conversation -- Part 1: Unsettled Selves -- The Unsettled Self: Creative Practice and the Nomadic Poetics of a Contemporary Flâneur -- The Place of Social Space: Classed Identities in a Regional Sporting Club -- From the Parlour to the Forum: How Dress-Art Unsettles Place and Space -- Part 2: Unsettling the Rural -- Rural 'Tourist' - Rural 'Resident' - Betwixt and Between Places and Spaces -- Disrupting Rural Futures and Teachers' Work: Problematising Aspirations and Belonging in Young People's Lives -- Ourselves, Our Rivals: Unsettling Communities During Rural School Consolidation -- Counter Hegemonic Food Discourses and Geographies of Food, Are We Losing the Rural? -- Kheti and Khadar: Land and Rights on an Agrarian Floodplain -- Part 3: The Unsettled City -- Unsettling Streetscapes: Everyday Occupations of Public Spaces in Karachi -- Citizens, Spatial Practices and Resurrection of the Idea of Place in Contemporary Lucknow -- At Home in the City: Educated Women, Housing and Belonging in Port Moresby -- Unsettling the Settler City: Indigenous Commemoration in Central Melbourne -- Part 4: Space, Place, Absence -- Unsettling Post-War Settlement: Remembering Unassimilable Families in the Space of the Migrant Camp -- "From Riverbank Humpy to White House": Spatial Assimilation at Rumbalara in 1950s Victoria -- The Unsettled Places of Rewilding -- Haunting Absence: Treblinka and Birkenau -- "Those Asian Kids": Race/Ethnicity, Invisibility and Absence in an Australian Classroom.
Keywords: Sociology -- Methodology; Social sciences; Humanities; Educational sociology; Human geography; Communication; Developmental psychology; Sociological Methods; Humanities and Social Sciences; Sociology of Education; Human Geography; Media and Communication; Developmental Psychology